2020
DOI: 10.1044/2019_jslhr-19-00162
|View full text |Cite|
|
Sign up to set email alerts
|

Early Speech and Language Development in Children With Nonsyndromic Cleft Lip and/or Palate: A Meta-Analysis

Abstract: Objective The aim of the study was to conduct a meta-analysis of research examining the early speech and language functioning of young children, birth to age 8;11 (years;months), with nonsyndromic cleft lip and/or palate (NSCL/P) compared to their peers without NSCL/P. Method We conducted a random-effects metaregression using 241 effect sizes from 31 studies comparing 955 young children with NSCL/P to 938 typically developing peers on measures of speech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 67 publications
2
38
3
1
Order By: Relevance
“…The development of speech sounds directly influences the words that a child uses in their vocabulary, meaning that the more sounds produced early on will lead to a greater early vocabulary as the child develops. The consequences of these early delays are not known, but studies have shown that children born with a cleft perform poorly compared to peers in tests of language [26,27]. Although the presence of cleft articulation errors at 12-months was not found to be a significant predictor in this study, the early identification of non-oral and posterior articulation in very young children is of benefit in order for SLPs to provide timely intervention before these patterns become entrenched.…”
Section: Discussioncontrasting
confidence: 55%
“…The development of speech sounds directly influences the words that a child uses in their vocabulary, meaning that the more sounds produced early on will lead to a greater early vocabulary as the child develops. The consequences of these early delays are not known, but studies have shown that children born with a cleft perform poorly compared to peers in tests of language [26,27]. Although the presence of cleft articulation errors at 12-months was not found to be a significant predictor in this study, the early identification of non-oral and posterior articulation in very young children is of benefit in order for SLPs to provide timely intervention before these patterns become entrenched.…”
Section: Discussioncontrasting
confidence: 55%
“…A catch-up due to maturation is reported, resulting in non-significant differences compared to language competence in non-cleft peers (Boyce, Kilpatrick, Reilly, Da Costa, & Morgan, 2018;Collett, Leroux, & Speltz, 2010). In a recent meta-analysis, the conclusions were similar, after examining the literature (n=31) on speech and language development in children with nonsyndromic cleft lip ± palate from 1950 to 2018, including ages 0 through 8:11 (Lancaster et al, 2020). Both expressive and receptive language competence were examined, resulting in an average effect size of -0.57 SD unit lower for expressive language competence and -0.59 SD unit lower for receptive language skills for children with non-syndromic CP±L compared to competence of peers without clefts.…”
Section: Cleft Palate ± Lip and Comorbiditymentioning
confidence: 91%
“…Both expressive and receptive language competence were examined, resulting in an average effect size of -0.57 SD unit lower for expressive language competence and -0.59 SD unit lower for receptive language skills for children with non-syndromic CP±L compared to competence of peers without clefts. The overall conclusion about language development and competence in children with non-syndromic CP±L was that of early onset language delay but with a decreasing negative impact over time (Lancaster et al, 2020). However, two studies not included in the analysis targeting language competence in preschool and early school-aged children with non-syndromic CP±L reported DLD in 14% to 20% (Klintö et al, 2019;Morgan et al, 2017), indicating that there are both children with and without cooccurring DLD in the heterogeneous group of children born with non-syndromic CP±L.…”
Section: Cleft Palate ± Lip and Comorbiditymentioning
confidence: 97%
“…Children with CP+L experience a higher prevalence of OME which is often associated with a conductive HL (Flynn et al, 2009;Tengroth et al, 2020). Nevertheless, hearing within CP+L literature has not been consistently reported and remains an unexplained variance in speech outcomes (Sparks Lancaster et al, 2020). Compared to children with normal hearing, children with CP+L, as well as children with hearing impairment demonstrate restrictions in their early consonant development.…”
Section: Introductionmentioning
confidence: 99%